Clean energy access: Gender disparity, health, and labour supply - Anjali P. Verma; Imelda Imelda (Graduate Institute of International and Development Studies, 2022)
Women bear a disproportionate share of the health and time burden associated with lack of access to modern energy. We study the impact of clean energy access on adult health and labour supply outcomes by exploiting a nationwide rollout of a clean cooking fuel program in Indonesia. We find that access to clean cooking fuel led to an improvement in women's health and an increase in their work hours. We also find an increase in men's work hours and in their propensity to have an additional job, primarily in those households where women accrued the largest program benefits.
Keywords: H51; I15; I18; J22; O13; Q48; Q53; 330; gender inequality; energy access; health; labour supply; Indonesia